2001
DOI: 10.1159/000047484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long–Term Consumption of a Probiotic Bacterium, <i>Lactobacillus rhamnosus</i> GG, in Milk on Dental Caries and Caries Risk in Children

Abstract: Lactobacillus rhamnosus GG, ATCC (LGG), has shown antagonism to many bacteria including mutans streptococci. This randomized, double–blind, placebo–controlled intervention study was designed to examine whether milk containing LGG has an effect on caries and the risk of caries in children when compared with normal milk. 594 children, 1–6 years old, from 18 municipal day–care centres were included. The children received the milk with meals from coded containers 5 days a week in the day–care centres for 7 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
318
4
22

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(371 citation statements)
references
References 15 publications
11
318
4
22
Order By: Relevance
“…Most of the documented benefits of probiotics are associated with gastrointestinal disorders, including those caused by Clostridium difficile and antibiotic medication causing diarrhea (Vanderhoof et al, 1999;Szajewska and Mrukowicz, 2001;Cremonini et al, 2002;D'Souza et al, 2002), acute infectious diarrhea and irritable bowel syndrome (Camilleri, 2006;Quigley, 2007;Kligler and Cohrssen, 2008). Positive effects of probiotics were also observed for caries-associated risk factors (Näse et al, 2001;Ahola et al, 2002;Ç aglar et al, 2006;Cildir et al, 2009) and the colonization of the oral cavity by Candida spp. (Hatakka et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Most of the documented benefits of probiotics are associated with gastrointestinal disorders, including those caused by Clostridium difficile and antibiotic medication causing diarrhea (Vanderhoof et al, 1999;Szajewska and Mrukowicz, 2001;Cremonini et al, 2002;D'Souza et al, 2002), acute infectious diarrhea and irritable bowel syndrome (Camilleri, 2006;Quigley, 2007;Kligler and Cohrssen, 2008). Positive effects of probiotics were also observed for caries-associated risk factors (Näse et al, 2001;Ahola et al, 2002;Ç aglar et al, 2006;Cildir et al, 2009) and the colonization of the oral cavity by Candida spp. (Hatakka et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…Several clinical studies demonstrated that a regular consumption of probiotic lactobacilli and Bifidobacterium decreased the number of cariogenic streptococci in saliva and dental plaque, resulting in a significant lower risk of caries (Näse et al, 2001;Ahola et al, 2002;Ç aglar et al, 2006;Ç aglar et al, 2007;Cildir et al, 2009). Several studies also revealed that probiotic Lactobacillus strains were reducing gingival inflammation (Krasse et al, 2006;Twetman et al, 2009), improving periodontal health (Shimauchi et al, 2008) and decreasing the concentration of black-pigmented rods including Porphyromonas gingivalis in saliva and subgingival plaque (Ishikawa et al, 2003;Matsuoka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…8,21,22,23 Some studies of the effects of lactobacillus-based probiotics on mutans streptococci reported significant reductions in the levels of salivary mutans streptococci immediately after terminating daily intake. 8,21,22,23 The post-treatment reductions were not directly dependent on the delivery vehicles, which included milk, cheese, yogurt, lozenges, and straws prepared with freeze-dried strains. Çaglar et al 8 investigated whether slowly melting tablets facilitate a more thorough contact between the probiotic and the oral environment compared with a direct swallowing pattern from a straw.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomised, double-blind, placebo-controlled intervention study in 594 children, milk containing LGG reduced dental caries and the counts of mutans-streptococci after 7 months. Consequently, the risk of caries was significantly reduced [75]. In another double-blind, placebo-controlled trial of milk supplemented with fluoride and/or L. rhamnosus the effect on primary root caries lesions was investigated.…”
Section: Thereforementioning
confidence: 99%